ANALISIS UNJUK KERJA KOLEKTOR UDARA PENGERING KAYU BERSUMBER ENERGI SURYA - BIOMASSA - Sumarsono, Markus; Mustafa, Rivai (Badan Pengkajian dan Penerapan Teknologi, 2008)
A solar air-heating collector having a surface area of 230.4 m2 has been installed and integrated to a drying chamber to dry wood of 100 m3. The collector was classified as a matrix type collector with its absorber was made from black carbon fiber sheet. Collector worked together with a biomass boiler to supply heat to dryingchamber. The test results indicated that the thermal efficiencies of collector per batch were around 20%-31%.